CXCR5+TIM-3-PD-1+ stem-like cytotoxic CD8+ T cells: elevated in chronic rhinosinusitis and associated with disease severity - Liu, Zhichen; Zhao, Zixuan; Xie, Huanxia; Lu, Ning; Liu, Jisheng; Jiao, Qingqing (Frontiers in Immunology, 2024)
Background: Chronic rhinosinusitis (CRS) is a chronic inflammatory disease with an autoimmune background. Altered expression levels of T cell immunoglobulin and mucin-domain containing-3 (TIM-3), C-X-C chemokine receptor type 5 (CXCR5), and programmed cell death protein 1 (PD-1) are implicated in the progression of inflammatory and autoimmune diseases. Moreover, CXCR5+TIM-3-PD-1+ stem-like cytotoxic T cells function as memory stem cells during chronic disease processes and retain cytotoxicity-related gene networks. Objectives: To explore the expressions of CXCR5, TIM-3, and PD-1 on T cells and their correlation with clinical parameters in CRS. Methods: Flow cytometry was used to assess the expressions and co-expressions of CXCR5, TIM-3, and PD-1 on T cells in the tissues of the paranasal sinus and peripheral blood of patients with CRS as well as healthy controls. Immunofluorescence was used to assess the co-localization of TIM-3, CXCR5, and PD-1 with T cells. The disease severity of our patients with CRS was evaluated using the Lund-Mackay score. A complete blood count was also performed for the patients with CRS. Results: Expression levels of CXCR5 and PD-1 on T cells were significantly increased in the nasal tissues of patients with CRS. Compared with those in healthy controls, patients with CRS had high percentages of CXCR5+TIM-3-PD-1+ CD8+ and CD4+ T cells in nasal tissues, while no significant difference was observed in peripheral blood levels. Patients with CRS had a higher density of nasal CXCR5+TIM-3-PD-1+ T cells than that in healthy controls. CXCR5+TIM-3-PD-1+ CD8+ T cell levels in the nasal polyps of patients with CRS were negatively correlated with the patients’ Lund-Mackay scores. The levels of CXCR5+TIM-3-PD-1+ T cells in nasal tissues were also negatively associated with disease duration and positively associated with the chronic inflammatory state of CRS. Conclusions: The level of CXCR5+TIM-3-PD-1+ stem cell-like T cells, especially CXCR5+TIM-3-PD-1+ CD8+ T cells, is increased in CRS. Therefore, inducing CXCR5+TIM-3-PD-1+ T cell exhaustion may be an effective immunotherapy for CRS.